INNOVATION AND IMPLEMENTATION OF ADAB CURRICULUM: TA’DIB EDUCATION APPROACH IN CHARACTER FORMATION - Ashari, Arif Usman; Usman, M; Khuriyah, Khuriyah (Islamic Management: Jurnal Manajemen Pendidikan Islam, 2025)
Character education is very important in the world of education. The development and implementation of a character education curriculum will influence learning activities and the output/outcome produced. This article will describe the innovation and implementation of the adab curriculum at the Ar-Risalah Surakarta Integrated Islamic Elementary School (SDIT) using a ta'dib education approach. This study was conducted using a descriptive qualitative method, employing techniques such as interviews, observations, and documentation. Data analysis utilized qualitative data analysis techniques, including data condensation, data presentation, and drawing conclusions (Miles & Huberman). The findings of this study include: 1. SDIT Ar-Risalah Surakarta innovated the adab curriculum by independently developing an adab curriculum consisting of adab towards oneself, adab towards others, and adab towards the environment. Adab education was incorporated into the intraschool curriculum with an allocation of two hours of class time every week. 2. The implementation of the adab curriculum at SDIT Ar-Risalah Surakarta is divided into three stages: a. the socialization stage, where the adab education program is presented to the entire school community to establish a shared understanding and synergy in its implementation; b. the implementation stage, where adab education is conducted using the concept of ta'dib education as a process of instilling adab and placing students in their proper place, namely at the pinnacle of morality, adab, and ethics. c. The evaluation stage of adab education by conducting assessments to determine whether students have understood the material and are practicing adab education in their daily lives. Key findings from this study indicate that adab education designed independently and implemented systematically can be an effective strategy in shaping students' character. By applying the concept of ta'dib, schools ensure that adab education is not only theory-based but also oriented toward practical application in daily life.